ANALISIS ASAM LEMAK RUMPUT LAUT Ulva reticulata Forsskal YANG DIPEROLEH DARI PANTAI SEGARA SANUR - Ni Made Puspawati; Ni Gusti Ayu Made Dwi Suastuti; Dewa Ayu Indra Dewi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
Lipid content and fatty acid composition of seaweed Ulva reticulata Forsskal obtained from Segara Sanur Beach have been analyzed. Lipid was extracted from this seaweed using soxhlet extractor with chloroform:methanol (2:1) as solvent, while the composition of fatty acid was analysed using gas chromatrography accomplished by a mixture of 37 standard fatty acids (ST37AL85.D01). It was found that Ulva reticulata Forsskal contained (1,41±0,04)% (w/w) of crude lipids. The crude lipid was composed of 11 major fatty acids including pentadecanoic acid (12,08%), heptadecanoic acid (40,00%), cis-10-heptadecenoic acid (4,37%), oleic acid (1,77%), linolelaidic acid (4,31%), linoleic acid (13,01%), arachidic acid (4,71%), g-linolenic acid (2,27%), heneicosanoic acid (7,58%), cis-11,14-eicosedienoic acid (8,19%), and cis-8,11,14-eicosetrienoic acid (1,71%).